KOORDINASI ANTAR LEMBAGA PEMERINTAH DALAM PELAYANAN E-KTP DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Nurhidayat M; Sitti Nurmaeta; Rudi Hardi (Department of Government Studies Universitas Muhammadiyah Makassar, 2013)
This study aimed at knowing the Coordination of Inter-government institutions in Electronic ID-card Services as well as at knowing the supporting and obstacles factors of the Coordination of Inter-government institutions in the Electronic ID-card Services in Rappocini district of Makassar . This research wasadescriptive – qualitative, the population in this research are also as sample of 31 people . Data were collected by observation , questionnaires and interviews developed by the respondent . The data were analyzed descriptive qualitatively in which analyzing all data collected by the authors, then presented in the form of frequency tabulation completed by respondents’ idea obtained from the informants , interviews , and questionnaires . The results showed the Coordination of Inter-Government institutions in Electronic ID-card service in the Rappocini district of Makassar categorized as less effective and influenced by several supporting and inhibiting factors. The inhibiting factor in Electronic ID-card services , namely : (a). Lack of computer facilities and infrastructure devices in regard to the number of mandatory for Electronic ID-card. (b). communities took low active role to queue for electronic ID-card service. (c). Less proposionality of the operator of Electronic ID-card in carrying on its duties and responsibilities. While the supporting factors in Electronic ID-card services, namely: (a). The presence of regulations on population policies in the service of Electronic ID-card, (b). The presence of a proportional local budget from the central government to distribute in any subdistricts in Makassar. Penelitian ini bertujuan Untuk mengetahui Koordinasi Antar Lembaga Pemerintahan Dalam Pelayanan E- KTP serta untuk mengetahui faktor-faktor yang menjadi pendukung dan penghambat Koordinasi Antar Lembaga Pemerintah Dalam Pelayanan E-KTP di Kecamatan Rappocini Kota Makassar. Penelitian ini adalah Deskriptif-Kualitatif, Populasi dalam penelitian sekaligus merupakan sampel sebanyak 31 orang. Data dikumpulkan dengan menggunakan teknik berupa observasi, kuesioner serta dikembangkan dengan wawancara kepada responden. Data tersebut dianalisis secara Deskriptip kualitatif yaitu menganalisis semua data yang berhasil dikumpulkan penulis, dan selanjutnya disajikan dalam bentuk tabulasi frekuensi dilengkapi dengan tanggapan responden yang diperoleh dari hasil Informan, wawancara, dan kuesioner. Hasil penelitian menunjukkan Koordinasi Antar Lembaga Pemerintah dalam pelayanan e-KTP di Kecamatan Rappocini Kota Makassar dikategorikan kurang efektif dan dipengaruhi oleh beberapa faktor pendukung dan penghambat. Adapun Faktor penghambat dalam Pelayanan e-KTP yaitu : (a).Kurangnya sarana dan prasaranan perangkat komputer di banding jumlah wajib e-KTP. (b).Rendahnya peran aktif masyarakat ikut antrian dalam pelayanan e-KTP. (c).Kurang proposionalnya operator e-KTP dalam melaksanakan tugas dan tanggung jawab. Sedangkan yang menjadi faktor pendukung dalam pelayanan e-KTP yaitu : (a).Adanya regulasi tentang kebijakan kependudukan dalam pelayanan e-KTP, (b). Adanya anggaran APBD yang proposional dari pemerintah pusat untuk distribusikan setiap Kecamatan yang ada di Kota Makassar.